2009
DOI: 10.4081/922
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-instability test as a specific marker of malignancy and its application to detect cancer clones in borderline malignancy

Abstract: Recent progress in cytogenetic and biochemical mutator assay technologies has enabled us to detect single gene alterations and gross chromosomal rearrangements, and it became clear that all cancer cells are genetically unstable. In order to detect the genome-wide instability of cancer cells, a new simple method, the DNA-instability test, was developed. The methods to detect genomic instability so far reported have only demonstrated the presence of qualitative and quantitative alterations in certain specific ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…[8] In oncology, in vitro fluorescence labelling techniques have become increasingly interesting because they allow the determination of tumour malignancy, [9] chromosomal abnormalities, [10] metastatic disposition of tumours, [11] tumour oxygenation and pH, [12] tumour-induced angiogenesis, [13] gene deletions, duplications and amplifications [14] and also apoptosis versus necrosis imaging in cancer cell lines. [15] An emerging application of fluorescent compounds is diagnostic imaging in vivo, which allows an estimation of the metastatic disposition of tumours, [16] the detection of tumour-associated enzymes [17] and single cells in living orAbstract: Fluorescent probes are of increasing interest in medicinal and biological applications for the elucidation of the structures and functions of healthy as well as tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In oncology, in vitro fluorescence labelling techniques have become increasingly interesting because they allow the determination of tumour malignancy, [9] chromosomal abnormalities, [10] metastatic disposition of tumours, [11] tumour oxygenation and pH, [12] tumour-induced angiogenesis, [13] gene deletions, duplications and amplifications [14] and also apoptosis versus necrosis imaging in cancer cell lines. [15] An emerging application of fluorescent compounds is diagnostic imaging in vivo, which allows an estimation of the metastatic disposition of tumours, [16] the detection of tumour-associated enzymes [17] and single cells in living orAbstract: Fluorescent probes are of increasing interest in medicinal and biological applications for the elucidation of the structures and functions of healthy as well as tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…From a Western point of view, the final diagnosis rests on examination of the surgical or ESD specimen, because there is some possibility of cancer even if the diagnosis is LGD or HGD [21,23,36,[46][47][48]. Some studies have indicated that LGD and HGD should be treated, because genomic instability may already be present [49][50][51][52]. However, the European guidelines recommend reassessment with biopsy sampling and surveillance at 6-month to 1-year intervals for patients with HGD in the absence of endoscopically defined lesions [8].…”
Section: Discussionmentioning
confidence: 99%
“…This attitude has become especially apparent during the last few years, when several papers have been published which deserve high interest from the viewpoint of both the improvement of methodology (Mazzini et al, 2003;Bottiroli et al, 2004;Cremer et al, 2004;Pederson, 2004;Marziliano ey al. 2005;Sheval et al, 2005) and the application to clinical research (Alexandrakis et al, 2005;Fukuda et al, 2005;Hirose et al, 2005;Soldani et al, 2005).…”
Section: Mg Manfredi Romaninimentioning
confidence: 99%